Parameters to estimate the metal dusting attack in different gases. (September 2022) - Schlereth, C.; Hack, K.; Galetz, M.C.
Abstract: The relation between the experimentally observed metal dusting attack and parameters calculated from the test conditions is analysed. Commercial alloys were exposed for nearly 1000 h at elevated pressure in four gas mixtures. The gases had a constant carbon activity regarding the synthesis gas and the Boudouard reaction. However, these parameters did not correlate properly with the observed aggressivity. Alternative descriptions by the CO/H2 ratio, the carbon activity after water gas shift reaction and at metastable equilibrium are discussed. The results show that the whole set of reactions between gas and solid needs to be considered to describe the complex system. Graphical Abstract: ga1 Highlights: aC (Syngas) and aC (Boudouard) are insufficient to predict the metal dusting attack. aC (metastable equilibrium) and CO/H2 provide a good description of mass loss rate. Carbon isoactivity lines in OCH diagrams allow a direct comparison of complex gases. Alumina formers 699 XA and Kanthal APMT were the most resistant to metal dusting.